Application and Data Integration Based on Services Oriented Architecture in Enterprise - Nilo Legowo; Atur Sumedi (Emerging Science Journal, 2023)
Business process changes occurred very often in organizations to maintain business continuity, which had an impact on information changes and process flow improvements. There are numerous companies that have problems managing data, information, and software applications, especially with the constant demands for employee information. This research objective is to integrate data and applications based on service-oriented architecture (SOA) by using the service-oriented modelling architecture (SOMA) software development method to solve the problem of producing updated and real-time information practically required by organization functions. This research result shows this implementation can help analyze the company's business model by generating information needs and service candidates that refer to SOA concepts. This implementation also gives a solid integration of in-house applications with different platforms and data sources from different databases with real time information. From a technical point of view, this implementation also reduces the duplication of business process functions and in-house application management, as well as simplifying and accelerating the creation of new or updating in-house applications related to new information requirements of the company. It was found that the SOMA framework can also be employed as a reference for companies developing future applications with SOA basics. Doi: 10.28991/ESJ-2023-07-02-011 Full Text: PDF